Research on Wine Marketing Innovation Based on Internet - Changjiang Liu (2022)
Internet marketing refers to the use of modern information technologyandtheinteraction of Internet media to broaden the marketing channels of enterprises basedontheInternet, a new model of corporate marketing. This model has played a positive roleinpromoting enterprises to expand their marketing scale, market share andbrandawareness. The advent of the Internet economy has changed people's consumptionhabitswith the rise of the online shopping power of the new generation of consumers that hascontinuously increased online retail sales in China. With the development of the Internet, wine marketing is constantly innovating, creating a large number of emerging e-commercewine platforms. They have taken advantage of the unique power of the Internet that transformed the traditional marketing model. Finding its own blue ocean market in thewinesegment. In Portugal, wine network marketing is still in its infancy. Regardless of online andofflinesales, logistics and distribution systems, or the management of network marketingtalentsalready in place, they are all in an early stage. Therefore, the purpose of my researchistounderstand the characteristics of the Internet and explore the effects of network marketingonwine. The innovative role of marketing, and finally the importance of wine networkmarketing, I will study the wine marketing strategy from the perspective of network.Asawine company that has experienced brilliance and maturity, Changyu has a strongtypical significance. This article focuses on Changyu Wine Company as a case. Basedonthedetailed analysis of Changyu Company’s marketing environment, advantages anddisadvantages, opportunities and challenges, this article proposes the marketing strategyofChangyu Wine under the networked background, and finally gives the offline andonlinesales, Logistics and distribution system, corporate network marketing talents andotherperfect suggestions, hoping to provide reference and help for Portuguese wine networkmarketing companies. I expect to provide reference for Portuguese wine network marketingcompanies.